Evaluating generative AI tools: A comparative guide for new users (2024)
One of the most prominent forms of artificial intelligence that has been made public is generative AI, which offers a fresh perspective and direction for numerous global sectors. The impact of this artificial intelligence model on nearly every business and how certain vocations can be pursued has garnered a large audience. This paper evaluates generative AI from an objective standpoint and proposes a comparison of some of its key tools to help new users solve problems in their daily lives, at work or at home. This highlights the significance of understanding and utilizing this kind of AI.